Pelatihan Bahasa Inggris bagi Masyarakat Kawasan Wisata Berbasis Alam dan Budaya Betawi di PBB Setu Babakan Jakarta - Warni, Silih; Apoko, Tri Wintolo (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service program is to improve the English competence of the community in the Setu Babakan Betawi Cultural and Natural-based Village, Jakarta. The English training is part of the efforts to pioneer English villages in the tourist destination area. This activity was carried out using a training method with English needs analysis and problems faced by the community related to English mastery through interviews, observations, tests and questionnaires as well as to develop English teaching materials for the surrounding community. This service involves community mobilizers, the manager of the Setu Babakan Betawi Cultural Village and the village community, especially teenagers who are active in youth organizations. The results of this activity show the passion and enthusiasm of the community to learn English and improve the community’s self-confidence as well as their English speaking skills in the context of daily conversation in the Setu Babakan Area. Thus, it is very important to do sustainable English training in response to initiate English village.